Web service discovery method based on semantic expansion - ZHANG Zheng; ZUO Chun; WANG Yu-guo (Tongxin xuebao)
A Web service discovery method based on semantic expansion was provided.It semantically expanded the conception of service description and service request.The semantic expansion way includes equivalent expansion,feature expansion and compose expansion.It gave the definition of extend semantic subsume during the period of input/output matching.The experiment tells that this algorithm can improve the recall while maintaining a high level precision.If sin-gle service can not match the service request,the way can attempt service composition to match service request.The heu-ristic algorithm based on H*changed the composition problem to searching problem.Because of the adoption of estima-tion function,the efficiency is improved distinctly.